A Comparative Study on the Financial Performance of Mutual Fund Schemes of Private Companies in India - J. Nenwani, Pinkiben (International Journal of Psychosocial Rehabilitation, 2020)
Financial performance of mutual fund schemes is a subjective measure of how well a firm can use assets from its primary mode of business and generate revenues. There are many different ways to measure financial performance of mutual fund schemes of private and public companies in India, but all measures should be taken in aggregation. This study may be useful to mutual fund companies to understand the major factor relating to the performance of mutual fund like returns and expenses, any mutual fund companies may work on major factor of risk covered and performance. Mutual fund investors can easily make out which mutual fund scheme is the better performer in the capital market by knowing average return, Sharpe Ratio, Treynor Ratio, Expense Ratio etc. Potential and future new entrants may be able understood the clear picture to the mutual fund companies. Investor can take benefit by clear picture of industry and particular schemes. The outcome of the said research may be one of the useful inputs for various stake holders of the society.